Electron and hole effective masses in heavily boron doped silicon nanostructures determined using cyclotron resonance experiments - D.V. Savchenko; E.N. Kalabukhova; B.D. Shanina; N.T. Bagraev; L.E. Klyachkin; A.M. Malyarenko; V.S. Khromov (Semiconductor Physics, Quantum Electronics & Optoelectronics, 2018)
We present the experimental and theoretical results of analysis of the optically- induced cyclotron resonance measurements carried out using the charge carriers in silicon (Si) nanostructures at 9 GHz and 4 K. Effective mass values for electrons were determined as m el ∗ = 0 . 93 m 0 and m el ∗ = 0 . 214 m 0 . The obtained value of the transversal mass is higher than that reported for bulk Si. Parameters defining the energy surfaces near the valence band edge for heavy and light holes were found to be equal: A = –4.002, B = 1.0, C = 4.025, and corresponding to the experimental effective masses obtained in three orientations of the magnetic field: m lh= 0 . 172 , m lh= 0 . 157 , m lh = 0 . 163 , and m hh= 0 . 46 , m ∗ [ 111 ] = 0 . 56 , m ∗ [ 110 ] = 0 . 53 . The obtained energy band parameters and effective masses for holes have coincided with those found in bulk Si. The average values of the relaxation time of the charge carriers are found to be: τ e,1 = 2.28⋅10 –10 s; τ e,2 = 3.57⋅10 –10 s; τ lh = 6.9⋅10 –10 s; τ hh = 7.2⋅10 –10 s, which are by one order of value larger than those obtained in bulk Si. The prolongation of the transport time for photo-excited electrons and holes can be explained by the spatial separation of electrons and holes in the field of the p + -n junction as well as by reduction of the scattering process due to the presence of boron dipole centers. Keywords: cyclotron resonance, effective mass, relaxation time, silicon nanostructure.